2019
DOI: 10.21093/ijeltal.v4i1.436
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Language Proficiency of Indonesian English Teachers

Abstract: This study reports an observation of the competencies of Indonesian secondary English teachers.  An intensive observation over a two-week workshop session was performed involving 38 English teachers, with this group comprising 18 SMP English teachers and 20 SMA English teachers. Three aspects of the observation were identified for this study: competence in oral English, competence in written discourse, and the ability to motivate students in the classroom. This study revealed that English teachers lacked pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…It is effective for students in general and lowpro ciency levels, yet, not for high-pro ciency students. These results manifested a discrepancy toward some empirical studies, which claimed that most treatments were neglected for low-pro ciency learners yet performed on those at high-pro ciency levels (Alqahtani, 2015;Alshammari, 2022;Budiharso, 2019).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…It is effective for students in general and lowpro ciency levels, yet, not for high-pro ciency students. These results manifested a discrepancy toward some empirical studies, which claimed that most treatments were neglected for low-pro ciency learners yet performed on those at high-pro ciency levels (Alqahtani, 2015;Alshammari, 2022;Budiharso, 2019).…”
Section: Discussioncontrasting
confidence: 72%
“…Renandya et al (2018) argued that pro ciency is a necessary prerequisite factor that in uences L2 learning; therefore, teachers should differ in the teaching and learning strategies for each learner with different pro ciency levels. Some studies have revealed that most treatments worked only for students with high pro ciency levels yet failed to address the core problem of students with low pro ciency levels (Alshammari, 2022;Alqahtani, 2015;Budiharso, 2019;McLean et al, 2020). The present study, hence, addresses the following research questions:…”
Section: Introductionmentioning
confidence: 89%
“…The fear of making a mistake during speaking will be eliminated as teachers create a comfortable learning environment (Aslan & Şahin, 2020), which play an important role in developing students" speaking skills (Salim et al, 2020;. Besides, practising more in English speaking will benefit the students as the lack of speaking practise results in insufficient use of oral language (Budiharso, 2019) The foreign volunteer program is in line with the scope of Indonesian Railway Polytechnic as a vocational university, which requires the students to have practice activity more than theory; ideally, it should be 60% practice and 40% theory. However, practising English in speaking skills is considered a challenge in the educational system in non-native learning environments (Almansour & Al-Ahdal, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that Indonesians still lack of English proficiency (Budiharso, 2019;Wulyani et al, 2019) leads literature to call the stakeholders to (Renandya et al, 2018) to participate in the acceleration of English. The most up-to-dated program which can be expected in known as MBKM (Merdeka Belajar -Kampus Merdeka) which has been implemented in the last 2 years now.…”
Section: Introductionmentioning
confidence: 99%